(untitled) (Research, Society and Development, 2023)
Indirect adhesive restorations are increasingly being part of the oral rehabilitation procedures. With the purpose to reduce and minimize the difficulties and simplify the cementing technique with conventional adhesive resin cements, it was introduced a resin cement called self-adhesive for presenting chemical adhesion to dental tissues, ceramic and metal surfaces without the need for etching and adhesive systems aplications. Some studies point out to the problems of degradation of cement during storage. The inhibitors and peroxides presented in the cement composition are organic chemical compounds and, therefore, are susceptible to degradation phenomena under storage. For all of these factors, the resin cements have limited storage period and changes in the mechanism of polymerization may occur during this period. The present study has been prepared containing some variables to research. All these variables are seeking to investigate the consequences of different activation protocols of polymerization and the accelerated aging of self-adhesive dual cured resin cements on the degree of conversion. As well as test the null hypothesis that the activation protocol of polymerization and the accelerated aging do not cause alteration in the degree of conversion of the material to be tested.